Position relationship and long sitting with complaints of low back pain during studies online at level II students ners study program at STIKes Santa Elisabeth Medan in 2022 - Barus, Mardiati; Rupang, Ernita Rante; Lahagu, Evan Juniman Putra (Institute of Accounting Research and Novation (IARN), 2023)
Low back pain (LBP) is pain that occurs in the lower back due to excessive body activity. Long sitting is a sitting posture for a long time. Sitting position is a good position in doing activities such as reading, watching, and writing. This study aims to analyze the relationship between position and length of sitting with complaints of low back pain during online lectures for second-level students on the Nursing Study Program at STIKes Santa Elisabeth Medan 2022. The research method used was a correlation research design with a Cross Sectional approach. The population in this study are 84 people. The sampling technique is the Total Sampling technique. Data is collected using a questionnaire and the statistical test used was Spearman Rank (Rho). There is no significant relationship between sitting position and the occurrence of complaints of low back pain (p-value = 0.606; r = 0.057). There is a significant relationship between length of sitting and the occurrence of complaints of low back pain (p-value = 0.000; r = 0.588). It is concluded that there was no relationship between sitting position and complaints of low back pain in level II students and there was a relationship between length of sitting and complaints of low back pain during online lectures for level II students of the Nursing study program at STIKes Santa Elisabeth Medan 2022.